PROGRAM FOR DRILLING WELLS AND WATER DISTRIBUTION TO OVERCOME THE ANNUAL DROUGHT DISASTER IN PANCOR VILLAGE, SAMPANG, MADURA - Lucky Andriyanto; Maulydia; Dedi Susila; Soni Sunarso Sulistiawan; Fajar Perdhana; M. Masrur Rizal; Ilham Rahmanto (Universitas Airlangga, 2023)
Clean water is an essential necessity for every living thing. This is because water plays a role in the metabolism of every living thing such as humans, animals and plants. In 2019, when the dry season came, the Sampang Regional Disaster Management Agency (BPBD) released about drought disasters in the area. BPBD has received reports from sub-districts regarding areas potentially affected by drought. The provisional data totaled 64 villages. The purpose of this community service activity is to overcome the problem of annual drought that has hit Sampang residents, especially the community at the As-Salamah Islamic Boarding School Foundation, West Tajjan Hamlet, Pancor Village, Ketapang District, Sampang Madura Regency. With the annual drought disaster that occurs, the Universitas Airlangga community service team plans to make an artesian drilled well that will work together with a team from the Sepuluh Nopember Institute of Technology. The making of this Drilled Well is expected to be useful for the community in the foundation area of the As-Salamah Sampang Islamic Boarding School as well as for the surrounding residents. In addition to the manufacture of drilled wells, a program will also be created to collect ablution water and rainwater (during the rainy season). This water reservoir can be used to irrigate plants so that plants can grow well even in the dry season.